Longevity defined as top 10% survivors and beyond is transmitted as a quantitative genetic trait - Niels van den Berg (Nature Portfolio, 2019)
While human lifespan is only moderately heritable, “getting old” runs in families. Here, van den Berg et al. study mortality data from three-generation cohorts to define a threshold for longevity and find that individuals have an increasing survival advantage with each additional relative in the top 10% survivors of their birth cohort.